Epigenetic changes induced by pesticide exposure reactivate LINE-1 retrotransposon in breast cancer and mammary epithelial cells - Miret, Noelia Victoria (2021)
Expression of long interspersed nuclear element-1 (LINE-1) is reactivated during breast cancer initiation and progression. Strong ligands of aryl hydrocarbon receptor (AhR) activate LINE-1 through the transforming growth factor-β1 (TGF-β1)/Smad pathway. Studies have linked breast cancer risk with pesticide exposure, including hexachlorobenzene (HCB) and chlorpyrifos (CPF), both weak AhR ligands which promote alterations in mammary gland and tumor growth in animal models. We examined the pesticides action on LINE-1 reactivation in MDA-MB-231 breast cancer cells and NMuMG epithelial breast cells, and we evaluated the role of TGF-β1 and AhR. Results show that 0.5 μM CPF and 0.005 μM HCB reduced the methylation of the 5´-UTR of LINE-1 and increased LINE-1 mRNA expression via Smad and AhR signaling in MDA-MB-231. Besides, 5 μM CPF and 0.005 μM HCB heighten ORF1p nuclear import, the protein encoded by LINE-1, through TGF-β1/Smad and stimulate DNA double-strand breaks. Disturbingly, 5 μM CPF and 0.005 μM HCB also enhanced LINE-1 mRNA levels in NMuMG cells. CPF effect was through AhR and TGF-β1, while HCB action depends only of AhR. In addition, both pesticides increased ORF1p expression and nuclear localization. In conclusion, HCB and CPF induce LINE-1 reactivation, not only in breast cancer cells but also in epithelial mammary cells, supporting the idea that pesticide exposure could promote epigenetic changes, contributing to cell transformation and tumorigenesis in breast cancer.